The Spectrum of Influenza in Children. (7th September 2022) - Hoy, Gregory; Kuan, Guillermina; López, Roger; Sánchez, Nery; López, Brenda; Ojeda, Sergio; Maier, Hannah; Patel, Mayuri; Wraith, Steph; Meyers, Alyssa; Campredon, Lora; Balmaseda, Angel; et al.
Abstract: Background: Children constitute an important component of the influenza burden and community transmission, but the frequency of asymptomatic infection and post-influenza sequelae at the community level is poorly understood. Methods: Two community-based prospective cohort studies (2011–2020, 2017–2020) and 1 case-ascertained study (2012–2017) were conducted in Managua, Nicaragua. Non-immunocompromised children aged 0–14 years with ≥1 influenza infections, determined by polymerase chain reaction and hemagglutination inhibition assay, were included. Results: A total of 1272 influenza infections occurred in the household-based portion of the study. Influenza infection was asymptomatic in 84 (6.6%) infections, and the asymptomatic fraction increased with age (1.7%, 3.5%, and 9.1% for ages 0–1, 2–4, and 5–14, respectively; P < .001). Of asymptomatic children, 43 (51.2%) shed virus, compared to 1099 (92.5%) symptomatic children ( P < .001). Also, 2140 cases of influenza occurred in the primary care portion of the study. Sequelae of influenza were rare, with the most common being pneumonia (52, 2.4%) and acute otitis media (71, 3.3%). A/H1N1 had higher age-adjusted odds of acute otitis media (odds ratio [OR] 1.99, 95% confidence interval [CI]: 1.14–3.48; P = .015) and hospitalization (OR 3.73, 95% CI: 1.68–8.67; P = .002) than A/H3N2. B/Victoria had higher age-adjusted odds of pneumonia (OR 10.99, 95% CI: 1.34–90.28; P = .026) than B/Yamagata. Conclusions: Asymptomatic influenza infection is much less common in children than adults, although viral shedding still occurs in asymptomatic children. Post-influenza sequelae are rare in children in the community setting, and virus strain may be important in understanding the risk of sequelae. Abstract : The full clinical spectrum of influenza in children, including frequency of asymptomatic infection and sequelae, is poorly understood. We found that asymptomatic infection in children is rare and age-dependent, and that the risk of sequelae depends on virus strain.